Income Mobility in Costa Rica, 2001-2007 - Rowe, Samuel (2014)
In this paper we study year-to-year intra-generational income mobility in Costa Rica. To do so we use a panel data set constructed from the Household Surveys for Multiple Purposes (2001-2007) that allows us to follow the same households and persons from year-to-year. We find that there is substantial year-to-year income mobility in Costa Rica, especially in the middle of the income distribution. We also identify the factors that most affect year-to-year income mobility in Costa Rica. We find that per capita income is conditionally convergent; low-income families are more likely to experience an increase in income than are high-income families. Aside from initial per capita income, the three most important factors that explain changes in per capita household income in Costa Rica are, in order of importance: (1) changes in the employment status of household members; (2) changes in the number of dependents (children, elderly and other non-working members) in the household; and (3) the education of household members, especially the household head.